ANALYSIS OF STUDENTS’ WORDS MISTAKE IN SKRIPSI EXAMINATION - Nurhaida Lakuana; Nindi Anisa (BABASAL English Education Journal, 2022)
This research purposes to find out what type of words mistake made by the students and the causes of mistake made by the students in skripsi examination especially in English Education Study Program. This research is a qualitative research by using documentation and interview as intruments. The researcher used audio recording in documentation to record the students' proposal seminar performance and the researcher asked some questions in interview by using the audio recording to record the students' answers. The researcher selected 6 students in a class as a sample. This data collection involved 6 students of English Education Study Program who finished their skripsi examination. The result of this research indicate that the common mistake are made by the students during skripsi examination such us hard to apply grammar rule, limited number of vocabulary, and not perfect in pronounciation and intonation. Also, the result of this research indicate the causes of students mistake during skripsi examination namely communication apprehension, test anxiety, lecturer’s characteristic, and psychological factors.